"Is social inclusion through PE, Sport and PA still a rhetoric?" Evaluating the relationship between physical education, sport and social inclusion. Issue 1 (1st January 2018) - Dagkas, Symeon
Abstract: This Special Issue is part of Educational Review 's Hall of Fame, comprising the journal's most read and highly cited papers. As part of this I will be critiquing a milestone paper within the field(s) of Sport, PE and (I will extend to) PA by Professor Richard Bailey. The paper has been amongst the most-cited in the journal and I have personally cited the paper numerous times in my own work thus far. Upon its original publication (nearly 13 years ago), the article (managed to provide a very useful distinction between PE and sport (and PA), which is important given the constant slippage between the terms in many articles since. In this response article, I will try to provide a brief summary of the paper from Bailey, but at the same time examine closely the notion of social inclusion through sport and PE by summarising work that has subsequently been conducted. I will conclude by summarising that some 13 years later spurious claims about effective inclusive practices through sport abound, and we still lack clear evidence to support the rhetoric about the ways in which sport and PE can contribute to social inclusion.